2011
DOI: 10.1111/j.1540-8167.2011.02066.x
|View full text |Cite
|
Sign up to set email alerts
|

End-Stage Renal Disease Predicts Complications in Pacemaker and ICD Implants

Abstract: ESRD markedly increases bleeding and device-related infections. The risk of both complications parallels the severity of CKD. Further research is needed to reduce adverse outcomes in this high-risk population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
83
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(92 citation statements)
references
References 41 publications
4
83
0
Order By: Relevance
“…In our present study, clinical characteristics specific to our HD patients were pacemaker implantation is predicted after weaning from cardiopulmonary bypass (CPB), epicardial permanent pacing wires (atrial and ventricular) should be implanted intra-operatively, because a permanent intravascular device is a potential risk for recurrent IE in HD patients. 9) The generator would be implanted after the operation when the infection is controlled and the IE is considered to be healed in order to prevent electrical device infection.…”
Section: Discussionmentioning
confidence: 99%
“…In our present study, clinical characteristics specific to our HD patients were pacemaker implantation is predicted after weaning from cardiopulmonary bypass (CPB), epicardial permanent pacing wires (atrial and ventricular) should be implanted intra-operatively, because a permanent intravascular device is a potential risk for recurrent IE in HD patients. 9) The generator would be implanted after the operation when the infection is controlled and the IE is considered to be healed in order to prevent electrical device infection.…”
Section: Discussionmentioning
confidence: 99%
“…Renal disease, and in particular end-stage kidney failure requiring dialysis, has been associated with higher mortality rates and infections in patients with pacemakers and ICDs. [12][13][14] The risk of excess mortality becomes evident at even a moderate level of renal dysfunction (<60 mL/min/1.73 m 2 ). 12 In our current prospective study, we found CKD to be a strong risk factor for mortality.…”
mentioning
confidence: 99%
“…47) Compared with controls, dialysis patients have markedly increased bleeding and device-related infections (12.5% versus 0.2%, P < 0.00001). 48) In light of this information, the high incidence of complications may offset the potential survival benefit of ICD implantation in patients with stage 5 CKD. Finally, the presence of comorbidities such as atrial fibrillation, wide QRS, older age, and severe heart failure may counteract the benefit of ICD implantation in dialysis patients.…”
Section: )mentioning
confidence: 99%